Transformation of Management Information Systems in the Digital Era: Integration of Big Data, Artificial Intelligence, and Strategic Decision-Making - Hapini Awang; Mazzlida Mat Deli (Yayasan Pendidikan Islam Al-Matani, 2025)
The rapid development of digital technologies has driven organizations to adopt Management Information Systems (MIS) that are more adaptive, intelligent, and integrated. MIS no longer functions merely as an administrative record-keeping tool but has evolved into a strategic system that supports real-time, data-driven decision-making. This article aims to examine recent developments in Management Information Systems within the context of digital transformation, with a particular focus on the integration of big data, artificial intelligence (AI), and predictive analytics. The method employed is a literature review of international scholarly publications and recent industry reports. The findings indicate that modern MIS significantly enhances managerial decision effectiveness, operational efficiency, and organizational competitiveness. These results underscore that strengthening MIS through intelligent technologies has become a strategic necessity for organizations in the digital economy era.